The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1002/rcm.3292
|View full text |Cite
|
Sign up to set email alerts
|

Metal–ligand solution equilibria studied by electrospray ionization mass spectrometry: correlation between ion intensity and acid–base equilibria in solution

Abstract: Electrospray ionization mass spectrometry (ESI-MS) is increasingly used in the study of metal-ligand equilibria in aqueous solutions. However, the correlation between conditions in solution and mass spectra in the gas phase is far from being completely established. In the present work the equation i = kC(0)f was used to correlate relative ion intensity (i) in an ESI mass spectrum, the stoichiometric concentration (C(0)) in solution of the complex which produced this ion, and the fraction (f) of complex having … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 17 publications
1
12
0
1
Order By: Relevance
“…In contrast to main-group metals, transition-metals are mostly in the form of metal complexes (Henderson & Evans, 1999;Di Marco et al, 2007) and metallocenes; not so many real organometallics that contain the covalent bond between carbon and metal is described.…”
Section: B Transition-metal Organometallic Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to main-group metals, transition-metals are mostly in the form of metal complexes (Henderson & Evans, 1999;Di Marco et al, 2007) and metallocenes; not so many real organometallics that contain the covalent bond between carbon and metal is described.…”
Section: B Transition-metal Organometallic Compoundsmentioning
confidence: 99%
“…These complexes are often formed by the metal complexation with amino acids, sugars, and drugs (Alvarez, Vartanian, & Brodbelt, 1997;Vaisar et al, 2005;Fournier et al, 2008). Their gas-phase ion-molecule reactions are often studied (Gatlin & Tureček, 1997;Lemr, Holčapek, & Jandera, 2000;Asmis & Sauer, 2007;Di Marco et al, 2007;MacAleese & Maitre, 2007;Mo et al, 2007;Tureček, 2007;Burgert & Schnockel, 2008;Jirásko et al, 2008;Polfer & Oomens, 2009). The most famous metal complexes are even naturally occurring, such as chlorophyll (Mg), hemoglobin (Fe), and myoglobin (Fe), and their presence in living organisms is indispensable (Wöhrle & Pomogailo, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…However, different molecular species may undergo different vaporization and ionization efficiencies. Response factors may also change with pH, further complicating quantitation [89]. This represents one of the biggest disadvantages of the ESI-MS method for binding-constant determination [90].…”
Section: Electrospray Ionization Mass Spectrometrymentioning
confidence: 99%
“…Recent studies on biological [94] and inorganic [89] systems concluded that the ESI-MS approach was useful for quantitative measurements of binding constants. However, a close reading shows that confidence in a quantitative result is warranted only if there is already available a considerable amount of information on the system.…”
Section: Electrospray Ionization Mass Spectrometrymentioning
confidence: 99%
“…Карактеристике комплекса метал лиганд и специјација зависе од pH, [141] јер комплекси мењају своје стање протоновања и наелектрисања са променом pH (показују или кисела или базна својства).…”
Section: проучавање комплексирања масеном спектрометријомunclassified